Lipid profile as a predictor of Neuropathy: The Sheffield Prospective Diabetes Study - Rajbhandari, Satyan; Hamid, Fahad Syed; Harris, Nigel; Tesfaye, Solomon (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Background : Despite being a very common complication, the aetiology and potential risk factors of diabetic neuropathy (DN) have not been clearly determined in a prospective study. Aims: The aim of Sheffield Prospective Diabetes Study was to identify the abnormalities of physiological, biochemical, haemorrhelogical and cellular function for complications of diabetes in type 1 diabetes.Materials and Methods: 66 newly diagnosed type 1 diabetic subjects (mean age 31 ± 9 (SD) duration (3 years ± 2) were identified and followed for 9 years. They had detailed neurological assessment (symptoms and signs score, nerve conduction, vibration perception threshold, warm thermal discrimination threshold and autonomic function tests) and blood samples taken for detail biochemical and haemorrheological analysis at base line and at follow up.Results: At the 9 years follow up, 51 subjects were studied of whom 18 were found to have DN using Dyck’s criteria. As expected subjects with DN had significantly higher (p